Strategi Peningkatan Daya Saing Sektor Jasa Konstruksi Di Indonesia: Institut Pertanian Bogor, Kementrian Perdagangan - Sri Retno Wahyu Nugraheni; Widyastutik; Syarifah Amaliah; Iskandar Panjaitan; Ika Yulisyawati; Florika Malau (IPB University, 2021)
The service sector is often associated with a countries economic's progress, where the more advanced a country, the greater its role in the service sector. Construction service is one of Indonesia's service sectors which has more than one forward and backward linkage value and shows that construction services are a key sector. However, the average growth of Indonesia's construction services exports during 2015-2020 was only 5.47 percent and still has the potential to be increased. Therefore, it is necessary to know the performance, comparative advantage, and competitive advantage of the construction services sector, which in turn needs to be formulated to increase the competitiveness of the sector. By using primary and secondary data, this study was analyzed using descriptive analysis, Export Product Dynamic (EPD), and Structural Equation Model (SEM). The results of the analysis show that the Indonesian construction services sector still has the opportunity to be developed as seen from the occurrence of excess demand, which indicates that the Indonesian construction market has not been fully exploited. The potential for developing exports of construction services with partner countries can be carried out by Indonesia with Australia, New Zealand, Japan, China, Korea, and several countries in Southeast Asia. The competitiveness of Indonesia's construction services sector is strongly affected by aspects of opportunity, regulation, and demand from partner countries. Therefore, several strategies that need to be carried out by Indonesia to increase the competitiveness of the construction services sector are determining priority partner countries, creating conducive conditions for political, security, economic, and business climate, strengthening and collaboration with Indonesian certification agency with the world of education, as well as strengthening business actors engaged in the service sector to be able to compete with competitors.